PENGARUH SELF REGULATED LEARNING DAN KONFORMITAS TEMAN SEBAYA TERHADAP PROKRASTINASI AKADEMIK SERTA IMPLIKASINYA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Ane Mulyani; Ade Rustiana; Ai Nur Solihat (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research problem of related to the low learning achievement of students. This research aims to determine the influence of self-regulated learning and peer conformity on academic procrastination and encourage it on student learning achievement in economics subjects. The research method used is a survey method with an explanatory research design. The population in this study was class XII IPS students at SMA Negeri 8 Tasikmalaya, totaling 155 people. The sampling technique used was saturated sampling technique. In this research, data collection was carried out using a questionnaire and the data analysis technique used was path analysis. The results show that: 1) Self-regulated learning has a significant effect on academic procastination. 2) Peer conformity has a significant effect on academic procastination. 3) Self-regulated learning has a significant effect on learning achievement. 4) Peer conformity peers have a significant effect on learning achievement. 5) Academic procastination has a significant effect on learning achievement. 6) Self-regulated learning has a significant effect on learning achievement through academic procastination. 7) Peer conformity has a significant effect on learning achievement through academic procastination.